GAYA KEPEMIMPINAN PEMIMPIN AKADEMIK : STUDI KASUS PERGURUAN TINGGI SWASTA DI BANDUNG - Natalia Noya; Wilson Bangun (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2025)
This study explores the dominant leadership styles among academic leaders in a private university in Bandung and their influence on administrative staff performance in the context of digital transformation. The research is grounded in the growing importance of adaptive, value-based, and technologically driven leadership to support higher education institutions in facing the challenges of globalization and digitalization. Using a quantitative approach, the study surveyed 30 administrative staff from various faculties and academic departments. Data were collected through structured questionnaires that measured three dimensions of academic leadership: transformational, transactional, and digital leadership. Validity and reliability analyses confirmed that all items used in the instrument were statistically valid and internally consistent (Cronbach’s Alpha > 0.9). Descriptive results revealed that transformational leadership was the most dominant style perceived by respondents, characterized by visionary direction, inspirational motivation, integrity, and support for professional development. Although transactional and digital leadership also received positive responses, some gaps were identified, such as limited involvement in addressing internal issues and inconsistent application of digital strategies. Based on the findings, it is recommended that academic leaders strengthen strategic vision, promote innovation and technology use, provide fair evaluation systems, and enhance feedback mechanisms. Active involvement in professional development initiatives is also crucial to foster a collaborative and high-performing academic environment. This research contributes to the understanding of effective academic leadership and provides practical recommendations for institutional improvement in the digital era.